The level of learning attitude, approach, and knowledge towards the performance of economics students - Salam, Syahrul Nizam; Che Amat, Muhammad Asyraf; Abdul Aziz, Farous Izwan; Rusli, Nadiah Rus Liyana (Secholian Publication, 2022)
This study aims to identify the level of learning attitude, learning approach, learning knowledge, and performance of STPM Economics students in Sabah. The performance of Economics students refers to positive changes in their behavioral competence or ability that can develop their self-improvement and help them achieve their goals. These changes are done through positive and productive self-development by improving their attitude, knowledge, and learning. The results showed that the level of learning knowledge is at a high level, the attitude to learning, learning approach and economic student performance are at a moderately high level. The implication of this study is that STPM Economics students can improve their performance by adopting a more positive attitude towards knowledge and approach to learning which they can then bring with them when they enter the working world.